Determinasi Beban Kerja, Budaya Organisasi dan Kepemimpinan terhadap Kepuasan Kerja Karyawan (Literature SDM) - Jumawan Jumawan; Dzaki Rafi Fauzan (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to build hypotheses regarding the relationship between variables which can later be used for further research within the scope of human resource management. The writing method in this research is qualitative (library research), where the data comes from previous research. Online media is also used to obtain previous research data such as Google Scholar, Publish or Perish and other academic media. The results of this research are: 1) Workload influences employee job satisfaction; 2) Organizational culture influences employee job satisfaction; and 3) Leadership influences employee job satisfaction.